Ethical Principles for Medical Student Recruitment in Education Research in Pakistan: A Systematic Review - Noori Kiran Naeem; Hamza Rana; Asfandyar Anwer; Zil- (University of Lahore, 2023)
Objective: With the increasing publication in medical education research in Pakistan, this systematic review aims to identify both addressed and un-addressed ethical issues for student recruitment in medical education research. Methodology: After key search terms finalisation selection criteria were defined for the systematic review. The finalised keywords were put in data bases of Pub-Med, Pakmedinet, and ERIC, revealing a total of 12084 articles. Google Scholar was used as grey literature search leading to 2509 articles. 10056 out of 10087 were removed upon initial screening. A total of 31 met the eligibility criteria according to PRISMA guidelines, out of which 23 were excluded leaving a final count of 8 articles to be included in the study. Results: The ethical issues identified in the selected studies were, Distributive Justice, Autonomy, Rights to withdraw, Coercion into Study, Confidentiality, Informed Consent, Equity in participant selection, Awareness of research participation. Four out of eight studies failed to openly declare the rights of the students to participate voluntarily, while five out of eight studies failed to declare students having rights to withdraw. Three out of eight studies lacked distributive justice of educational content among different groups whereas two studies lacked methodological rigor on participant selection. Conclusion: During the recruitment of students for research, researchers need to be aware of ethical issues and devise a strategy to address them. These issues should be thoroughly addressed before Institutional Review Boards approve data collection. Institutes promoting such research can train and educate researchers by practicing ethical research protocols.